Behavioural Analysis of a Residential Building Subjected to Influences of Discontinuous Ground Deformations: Case Study in the Upper Silesia, Poland - Szojda, Leszek; Kotala, Bernard (Archives of mining sciences = Archiwum górnictwa, 2025)
The end of the long-term exploitation of minerals makes it possible to stop maintaining underground infrastructure and pumping out water. This raises the groundwater table and may cause changes in the mechanical parameters of the subsurface soil layers. The occurrence of these phenomena in urban areas has raised concerns about the safety of residential buildings subject to such influences. The analysed two-storey building, without a basement, had a square plan and a typical brick wall structure with RC structural elements: foundation strips, inter-storey ceilings, ring beams on load-bearing walls and stairs. The numerical model also included the groundmass to consider the soil-structure interaction effect. During the calculations, all loads occurring during the standard operation of the building and two locations of the sinkhole under the building’s foundations were considered. The results of the analyses are presented in the form of colour maps showing the displacement of the building, the change in stresses in the soil under the foundations, the change in the principal stresses in the building structure and the possibility of cracks appearing. The analyses show that the building will not be destroyed, but there will be damage to the load-bearing walls.